La Tahzan = Jangan bersedih! / Aidh Al Qarni; penerjemah, Samson Rahman; penyunting, Syamsuddin TU, Anis Maftukhin, A.Khalis - AL-QARNI, Aidh; Khalis, A; Maftukhin, Anis; Rahman, Samson; Syamsuddin.TU (Qisthi Press, 2008)
xxviii,568 hlm 26 cm